PENETAPAN KADAR KALSIUM PADA SUSU BUBUK BERMEREK “H” SECARA TITRASI KOMPLEKSOMETRI - MUSTAFA R LUBIS (JURNAL ILMIAH KOHESI, 2018)
Powdered milk is a dairy product obtained by reducing a large portion of water through the process of drying fresh pasteurized milk or recombined milk, with or without the addition of vitamins, minerals, and food additives that are permitted. Powdered milk includes fatty, low fat and nonfat milk powder (BSN, 2006). The mix of branded "H" powder has flavor variants, namely chocolate, vanilla, green tea, green beans and belgian chocolate. In general, all milk powder products that are issued prioritize high calcium and low fat properties. Some variants of milk powder products are supplemented with chondroitin and glucosamine. When calcium nutrition is adequate for adults and seniors over 19 years, 800 mg / day, pregnant and lactating mothers are recommended to increase the consumption of calcium by 150 mg / day, infants and children 200 mg / day to 400 mg / day, while for adolescents it is 100 mg / day. Disease due to excess calcium is called hypercalcemia, which can cause calcium buildup where it should not. Calcium buildup can occur in cells and tissues, and can cause kidney stones. Calcium levels obtained from "H" branded milk powder are 0.24%.